The power of the wandering mind nondirective meditation in science and philosophy - Eifring, Halvor 1960- (Dyade Press, 2019)
Nondirective Meditation is not about emptying the mind. Instead, mind wandering is seen as an important resource. Silently repeating a meditation sound helps to cultivate a free mental attitude. The activity in the brain's default mode network increases, enriching the flow of spontaneous thought. Mind wandering brings rest and recuperation, helps us consolidate our memory of the past, and stimulates our planning toward future goals. It enhances creativity and makes it easier to shift perspective. It is a central feature of empathy and social relations. In fifteen chapters, experts in neuroscience, medicine, psychology, philosophy and the humanities share groundbreaking perspectives on how nondirective meditation interacts with brain and body, mind and culture.
Keywords: Transzendentale Meditation; Meditation